Case Report: Clinical pathological characteristics, diagnosis, and treatment analysis of eosinophilic solid and cystic renal cell carcinoma: experience from a five-case series - Zi, Guo Run; Feng, Run-lin; Guo, Xin; Zhang, Da-jiang; He, Dong-Lin; Ke, Chang-xing (Frontiers in Oncology, 2025)
BackgroundEosinophilic solid and cystic renal cell carcinoma (ESC-RCC) is a rare renal tumor subtype. Accurate diagnosis and effective management remain challenging due to its distinct but often overlapping features with other renal tumors. This study aims to characterize the clinicopathological features, management, and outcomes of a five-case series to improve diagnostic and therapeutic strategies for this entity.MethodsWe retrospectively analyzed five patients with pathologically confirmed ESC-RCC from 2020 to 2025. Data on clinical presentation, imaging, histopathology, immunohistochemistry (IHC), surgical management, and long-term follow-up were collected.ResultsThe majority of patients (4/5) presented with flank pain. Imaging revealed solitary, well-demarcated cystic–solid masses with progressive enhancement in solid components and a lack of enhancement in cystic areas. Histopathology consistently showed a mixed growth pattern with eosinophilic, hobnail-like cells and distinct perinuclear halos. IHC was crucial for diagnosis, with consistent CK20+/CK7−/CD117− immunoprofiles. While most patients had a good prognosis with surgical resection, our series also highlighted a young patient (29 years old) and cases with metastatic potential and recurrence.ConclusionESC-RCC exhibits a unique clinicopathological and immunophenotypic profile. Early detection and complete surgical resection are critical for a favorable outcome. The potential for metastasis and recurrence underscores the need for genetic testing (e.g., TSC gene mutations) and multidisciplinary collaboration to guide individualized treatment.